2013
DOI: 10.2147/ott.s51997
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical significance of IGF-1, IGFBP-3, and IGFBP-7 in serum and lung cancer tissues from patients with non-small cell lung cancer

Abstract: The expression and clinical significance of insulin-like growth factor 1 (IGF-1), insulin-like growth factor binding protein 3 (IGFBP-3), and insulin-like growth factor binding protein 7 (IGFBP-7) were investigated in serum and lung cancer tissues from 57 patients with non-small cell lung cancer (NSCLC). Lung cancer tissues at different pathologic stages (27 patients at stages I–II and 30 patients at stages III–IV), normal lung tissues from 17 patients with benign pulmonary disease, and serum samples from both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…The IGFR signaling pathway regulates cell growth and development, which is essential for normal lung development and growth [19,20]. As a multifunctional protein receptor, IGF2R can bind IGF2 at the cell surface and regulates the IGFR signaling pathway [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IGFR signaling pathway regulates cell growth and development, which is essential for normal lung development and growth [19,20]. As a multifunctional protein receptor, IGF2R can bind IGF2 at the cell surface and regulates the IGFR signaling pathway [21].…”
Section: Discussionmentioning
confidence: 99%
“…The staging system we used was the 7th edition of the TNM system [20]. All patients had received platinum-based chemotherapy after diagnosis and did not receive surgical treatment (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…In gastric cancer, transcripts for several collagens, including COLA11A1, are also up-regulated in malignant compared to pre-malignant tumors 28 and COLA11A1 is also up-regulated in cancer-associated fibroblasts of colon adenocarcinomas. 29 Insulin-like Growth Factor 1 (IGF1) is a key player in NSCLC tumorigenesis and metastasis, 30 initiating cell signaling, promoting mitosis, proliferation and differentiation, and inhibiting apoptosis. HBP1 is a transcriptional repressor that plays a role in Wnt signaling and induces cellular transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies indicate that a high concentration of blood-circulating IGF-1 (endocrine fraction) is a risk factor in numerous types of cancer, including colon cancer ( 20 ), prostate cancer ( 21 , 22 ), breast cancer ( 22 ) and non-small cell lung cancer ( 23 ). Although the level of circulating IGF-1 is affected by various factors, including growth hormones and IGFBP concentration, gender, age, ethnic group and nutritional status ( 24 ), studies have demonstrated that 38% of the variance in IGF-1 concentration among individuals is caused by genetic effects ( 24 ).…”
Section: Discussionmentioning
confidence: 99%